Tourism Transformation in the Digital Era: The Role of Information Technology in Enhancing Destination Competitiveness - RD. Hera Merdeka Khazinatul Khaeriah; Raden Aries Sofwan Zarkasih (SEAN Institute, 2026)
The development of information technology has driven significant transformations in the tourism sector, particularly in efforts to increase the competitiveness of tourist destinations in the digital era. This study aims to analyze the role of information technology in enhancing the competitiveness of tourist destinations and identify the various challenges faced in the digital transformation process of tourism. The research method used is a descriptive qualitative approach, with data collection techniques through literature reviews of books, scientific journals, policy reports, and publications related to digital tourism and smart tourism. The results indicate that information technology plays a crucial role in increasing destination visibility through digital marketing, enriching the tourist experience through the use of interactive technology, improving the efficiency of data-driven destination management, and facilitating access to and services for tourism. Furthermore, the transformation toward the concept of smart tourism provides added value for tourists and supports more sustainable destination management. However, the implementation of information technology still faces various challenges, including limited digital infrastructure, quality of human resources, readiness to adapt to technology, data security and privacy, unstandardized regulations, budget constraints, and changing tourist preferences. This study concludes that the successful use of information technology to increase the competitiveness of tourist destinations requires a comprehensive and collaborative approach between the government, industry players, and other stakeholders. Strengthening infrastructure, increasing human resource capacity, and adapting and integrated policies are key to supporting sustainable digital transformation in tourism.